Trophic interactions of vampire catfishes (Siluriformes: Vandelliinae) revealed by metabarcoding analysis of stomach contents. (2nd December 2021) - Bonato, Karine Orlandi; Silva, Priscilla Caroline; Carvalho, Fernando Rogério; Malabarba, Luiz Roberto
Abstract: The trichomycterid catfishes of the subfamily Vandelliinae, the candirus, are parasite fishes that feed on blood. Therefore, the trophic interactions and dynamics of food webs in aquatic systems involving these catfishes cannot be determined through visual analysis of stomach contents, and the parasite–host interactions in this group of fishes are mostly unknown, except for a few anecdotal or experimental observations. We used DNA analysis of stomach contents of these fluid‐feeding fishes to identify hosts and study the ecological interactions of the haematophagous species Paravandellia oxyptera . Specifically, we used sequences of the cytochrome oxidase I gene collected from the gut contents of the catfish and compared them to data from GenBank to identify the host species. Our analysis indicated that examined specimens of Paravandellia oxyptera were exclusively fish parasites, and we identified genetic markers from eight host species from five families and three orders based on stomach contents. Paravandellia oxyptera does not exhibit host specificity. Unlike mucophagous trichomycterids, host species of haematophagous P. oxyptera belong to different trophic levels, showing a wide spectrum of interactions in the food web. A comparison of the host species with the accompanying fauna collected during sampling allowed an association between host preference and host size. Barcode analysis of stomach contents further produced a secondary source of information on the diversity of fish in the study area. This is the first study to identify host species of haematophagous parasitic fishes through the analysis of gut contents, demonstrating that specimens obtained in natural environments show much larger spectra of ecological interactions than previously reported from anecdotal or laboratory observations. This research is of broad interest, and exemplifies how DNA barcoding analysis of stomach contents provides new and relevant information on parasite/host interactions, with results not obtained by traditional methods of stomach content analysis.